Pelatihan Membatik Guna Mengembangkan Keterampilan Berwirausaha pada Batik Tulis Salingka Tabek - Das, Nidia Anggreni; Defitri, Siska Yulia; Fitasari, Anggi Al; Daturrahmi, Sayyi; Dzakiyyah, Husni Taufiq; Putri, Aulia Nanda; Almina, Elsa Febri; Fatikasari, Difani; Fitri, Nadha Aulia; Hamdi, Chintia Devina; Nurlisafani, Nurlisafani; Salman, Andre (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This Community Service program aims to improve batik-making skills and foster an entrepreneurial spirit among students and the community, specifically through collaboration with Batik Tulis Salingka Tabek, Nagari Koto Baru, Kubung District, Solok Regency. This PKM uses a direct training method where, through material presentation and practice, participants learn about tools and materials, design models, wax application, dyeing, and the production of batik fabrics that are ready for sale. The training is not only related to the batik-making process but also introduces marketing strategies so that the value of the products can be added to and compete in the market. The results of this activity can be seen in the increased understanding of batik making among participants in the creation of hand-drawn batik. Participants can create designs independently and perform dyeing using natural dyes, as well as gain an understanding of entrepreneurship, where batik can be used as a promising business venture. In addition, this training also serves as a tool for cultural preservation and the development of the batik industry.